2019
DOI: 10.2147/cmar.s187316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisphosphonates on local recurrence of giant cell tumor of bone: a meta-analysis

Abstract: BackgroundGiant cell tumor of bone (GCTB) is a locally aggressive tumor, and its postoperative recurrence remains a problem. The present meta-analysis aimed to analyze the effect of bisphosphonates (BPs) on local recurrence of GCTB.MethodsSeven case–control studies were included by computerized searches of bibliographic databases (PubMed, AMED, EMBASE, the Cochrane library, ISI Web of Science, and China National Knowledge Infrastructure). The pooled adjusted ORs were calculated to evaluate the local recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…There were no cases with malignant transformation. The difference between the effects of orthovoltage and megavoltage with respect to the local failure, as reported in previous studies was also discussed in this article, which varies from 7% to 30% with megavoltage and as high as 63% with orthovoltage [65] .…”
Section: Radiotherapymentioning
confidence: 52%
See 1 more Smart Citation
“…There were no cases with malignant transformation. The difference between the effects of orthovoltage and megavoltage with respect to the local failure, as reported in previous studies was also discussed in this article, which varies from 7% to 30% with megavoltage and as high as 63% with orthovoltage [65] .…”
Section: Radiotherapymentioning
confidence: 52%
“…The secondary effects reported with BPs in patients with GCTB were a decrease in calcium levels, jaw osteonecrosis, fever and digestive upset. [65] Apparently, the type of bisphosphonate and previous dental procedures, may act as precipitating factors for jaw osteonecrosis [66] .…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…A recent meta-analysis showed bisphosphonate had beneficial effect on patients who underwent intralesional curettage. 11 However, Lipplaa et al reported adjuvant treatment with zoledronic acid did not decrease the recurrence rate of GCTB in the recent randomized control trial with 14 patients. 19 In our opinion, with the present evidence from the literature, an adequate intralesional tumor curettage is still the key in local tumor control and reducing LR in GCTB of extremities.…”
Section: Discussionmentioning
confidence: 95%
“…Bisphosphonates, like zoledronic acid (ZA), can be an option in the adjuvant setting. A recent meta-analysis of case-control studies showed that the use of adjuvant bisphosphonates in patients submitted to intralesional curettage may decrease local recurrence rates, independently of Campanacci staging [79]. In patients undergoing wide resection, bisphosphonates seem to have no benefit in local recurrence.…”
Section: Bisphosphonatesmentioning
confidence: 99%